Fractional-N PLL-Based Waveform Synthesis for FMCW SAR - Gwasira, Thomas (Department of Electrical Engineering, 2025)
Achieving high-quality transmitted and local oscillator signals is a core objective in the design and implementation of high-resolution radar imaging systems, as the reconstructed images depict the interaction of the signals with elements in the scene. This dissertation concerns optimisation of the imaging capabilities of a frequency modulated continuous wave (FMCW) synthetic aperture radar (SAR) system, named the miloSAR, by improving the frequency synthesis aspects of the system. This is done by considering the phase-locked loop (PLL) synthesiser employed and waveforms, thereof, in terms of dynamic response characteristics and frequency response characteristics. The dynamic response component entails studying parameters which include the modulation period, modulation bandwidth, sweep rate, pulse repetition frequency (PRF) and slew rate among others and their influence on SAR image quality of the system in question. It was discovered that to better the performance of the system as it relates to these parameters, the radar system and the synthesiser had to be modelled and characterised in order to realise more optimal waveforms such as the sawtooth waveform which previously was not possible owing to limited information on the PLL's dynamics. Furthermore, the signal acquisition system was redesigned to increase the data rate of the system from 11 MB/s to 43.231 MB/s, thus, allowing support for higher PRFs and sample rates. Frequency response characteristics involve stability of both the synthesiser and the generated waveforms. The main issues related to this were identified to be ramp non-linearity, spurs and phase noise. Phase noise was the primary concern for this work since sufficient ramp linearity was achieved by the synthesiser and spurs have been addressed in another author's work on the miloSAR. Two independent synthesisers were, in fact, used to realise the heterodyne architecture required for the miloSAR and they were observed to exhibit significant phase instability. Due to the range correlation filtering effect achieved by using the same clock as the reference inputs of the PLLs and the ADC clock, phase noise caused by strong targets was considered to be less of a concern. However, the phase noise skirt of antenna leakage was identified as a major cause of performance degradation since the leakage is high in power and its phase noise skirt, in regions where range correlation filtering does not occur, swamps weaker radar returns. This becomes an even bigger problem when the PLL bandwidth is increased to improve the PLL's dynamics. The insights from both perspectives of the waveform synthesis problem were combined to give an instructive conclusion on how waveform synthesis must be carried out for the miloSAR and recommendations for a more performant system were proposed.